Inhibition of the thyroid hormonogenic H2O2 production by Duox/DuoxA in zebrafish reveals VAS2870 as a new goitrogenic compound. (15th January 2020) - Giusti, Nicoletta; Gillotay, Pierre; Trubiroha, Achim; Opitz, Robert; Dumont, Jacques-Emile; Costagliola, Sabine; De Deken, Xavier
Abstract: Thyroid hormone (TH) synthesis requires extracellular hydrogen peroxide generated by the NADPH oxidases, DUOX1 and DUOX2, with maturation factors, DUOXA1 and DUOXA2. In zebrafish, only one duox and one duoxa gene are present. Using a thyroid-specific reporter line, we investigated the role of Duox and Duoxa for TH biosynthesis in zebrafish larvae. Analysis of several zebrafish duox and duoxa mutant models consistently recovered hypothyroid phenotypes with hyperplastic goiter caused by impaired TH synthesis. Mutant larvae developed enlarged thyroids and showed increased expression of the EGFP reporter and thyroid functional markers including wild-type and mutated duox and duoxa transcripts. Treatment of zebrafish larvae with the NADPH oxidase inhibitor VAS2870 phenocopied the thyroid effects observed in duox or duoxa mutants. Additional functional in vitro assays corroborated the pharmacological inhibition of Duox activity by VAS2870. These data support the utility of this new experimental model to characterize endocrine disruptors of the thyroid function. Highlights: Inactivation of duox or duoxa results in goitrous hypothyroidism in developing zebrafish larvae. The NADPH oxidase inhibitor VAS2870 is a new goitrogenic compound. Zebrafish Duox activity reconstituted in a cellular system is inhibited by the VAS2870 compound.